Effects of maturity stages and fermentation of cocoa beans on total phenolic contents and antioxidant capacities in raw cocoa powder - Yen, Dang Thi Kim; Ha, Nguyen Vu Hong (Vietnam Journal of Biotechnology, 2018)
Consumption of cocoa (Theobroma cacao L.) and cocoa products is associated with numerous health benefits due to their high levels of polyphenols and antioxidant capacities. In this study, changes of total phenolic contents (TPC) and antioxidant capacities (AC) of raw cocoa powder at four maturity stages, under different fermentation methods and fermentation duration of cocoa beans were investigated. The TPC and AC were measured using Folin–Ciocalteu and Trolox equivalent antioxidant capacity (TEAC)/ABTS assay, respectively. In term of maturity stages, the powder of unfermented cocoa beans harvested from the stage one contained significantly lower levels of TPC (6.39 ± 0.02 g CE/100 g DM) and AC (26.82 ± 0.13 mol TE/100 g DM) than those from the beans harvested from the stage two, three and four. For all maturity stages studied, fermenting cocoa beans increased antioxidant capacities of the raw cocoa powder. Cocoa fermentation using the commercial enzyme Pectinex® Ultra SP-L resulted in lower TPC but higher AC in comparison to those treated without enzymes, however prolonged fermentation time in cocoa beans significantly reduced TPC and AC in the powder. Strong correlations between TPC and AC of fermented samples with (R = 0.923) and without enzyme supplement (R = 0.942) were obtained. Two-way anova analyses showed that changes of TPC and AC of cocoa beans were dependent on maturity stages, fermentation methods and fermentation duration. As a conclusion, fermentation of cocoa beans harvested at the maturity stage two and three was found to be optimum for the high levels of AC and TPC attainment; fermented beans with commercial enzyme could be utilized to reduce labor cost by shortening the fermentation duration.